Mathematics Formulae for Engineers and Scientists (Penerbit Universiti Sains Malaysia, 2018)
This book provides easy and quick access to mathematics formulae for those who use them in their everyday work. It covers the basic mathematics formulae which are required by the undergraduates. It also covers the various formulae in topics such as Ordinary Differential Equations, Partial Differential Equations, Fourier Series, Probability and Statistics, Statistical Quality Control, Laplace Transform, Complex Numbers, Numerical Analysis, Vector Calculus and Matrix Algebra. This book is a useful reference for students at the institutions of higher learning who study engineering, science and technology. Practitioners of mathematics and researchers in various fields which require the use of mathematics will also benefit from this book.
Keywords: Mathematics -- Formulae.; elektronické knihy; electronic books